Making museums attractions to tourists: serious leisure, meaningfulness and emotions as drivers to engagement - Loureiro, S. M. C. (2018)
The aim of this study is to explore the relationships among the concepts of serous leisure, meaningfulness, emotions, word-of-mouth and passionate desire, as antecedents and outcomes of engagement with museums. The proposed model is tested with a sample of 461 visitors (from Portugal and abroad) in a culturally specific setting of Lisbon museums (where improvements and innovations were implemented). The findings contribute to a better understanding of visitors’ perceptions about museums acting as tourist attractions. Several implications can be pointed out from the study findings, and interesting directions for future research are provided.